Baseline Survey Data on Crop Insurance Uptake and Agricultural Practices Among Smallholder Farming Households in Kenya. - Wanjau, Agnes Njambi; Ageyo, Collins Odhiambo; Otieno, Felix Owino; Mwungu, Chris Miyinzi; Ghosh, Aniruddha (2024)
This household survey was conducted among smallholder farmers in five Kenyan counties in May 2023. The project aimed to assess current crop insurance practices and willingness to adopt crop insurance solutions, such as satellite-based Soil Moisture Index and Picture-Based Insurance (PBI). Other topics covered included household and farm characteristics, poverty, agricultural and livestock production, and food security. The five counties covered by the project included Bungoma, Busia, Makueni, Embu, and Uasin Gishu. As part of the anonymization process, household identity variables such as phone numbers, GPS coordinates, individual names, and village names were removed and stored securely to ensure participants' confidentiality.